(untitled) (New York, 2007)
The book brings together information on harvest methods, system productivity, and methods for conducting safe, efficient, and environmentally acceptable operations in tropical forests. It highlights the challenges of harvest operations in the tropics, includes techniques that have been shown to be successful, and discusses newer technologies. The book is a reference for those interested in planning and management of tropical forests. Numerical examples are provided to provide clarity for interpreting graphs, procedures, and formulas. The book covers harvest systems from planning for felling to log transport from the forest, and concludes with considerations in selecting the appropriate harvesting technology
Keywords: Khai thác gỗ,Quản lý rừng,Logging,Forest management,Sustainable forestry; Vùng nhiệt đới,Vùng nhiệt đới,Tropics,Tropics,Tropics